Cytogenetic studies on the endemic Beyşehir nase, Chondrostoma beysehirense (Bogutskaya, 1997) in Turkey. Issue 2 (2nd April 2016) - Arslan, Atilla; Gündoğdu, Hayriye
Abstract: We present detailed cytogenetic properties of the Beyşehir nase, Chondrostoma beysehirense from Lake Beyşehir investigated through conventional Giemsa staining, C-banding and Ag-NOR in 10 specimens. The diploid number of chromosomes was 50, and the chromosomes in karyotypes were distinguished as metacentric, submetacentric/subtelocentric and acrocentric. Morphologically differentiated sex chromosomes could not be recognized. A secondary constriction was observed on the short arm of the sixth submetacentric chromosome pair. Some chromosomes had centromeric and pericentromeric C-bands, and the short arm of the sixth submetacentric chromosome pair was entirely C-positive. The active NOR was localized on the short arm of the sixth submetacentric chromosome pair, and this active NOR was associated with a large C-heterochromatin region. This NOR was recorded in all specimens examined and it occurred always in the homomorphic state on both homologous chromosomes. Systematics of Chondrostoma species will be better understood by using both molecular and FISH techniques in the future.